Community size can affect the signals of ecological drift and niche selection on biodiversity - Tadeu Siqueira; Victor S. Saito; Luis M. Bini; Adriano S. Melo; Danielle K. Petsch; Victor L. Landeiro; Kimmo T. Tolonen; Jenny Jyrkänkallio‐Mikkola; Janne Soininen; Jani Heino (Ecology, 2020)
Ecological drift can override the effects of deterministic niche selection on small populations and drive the assembly of some ecological communities. We tested this hypothesis with a unique data set sampled identically in 200 streams in two regions (tropical Brazil and boreal Finland) that differ in macroinvertebrate community size by fivefold. Null models allowed us to estimate the magnitude to which β‐diversity deviates from the expectation under a random assembly process while taking differences in richness and relative abundance into account, i.e., β‐deviation. We found that both abundance‐ and incidence‐based β‐diversity was negatively related to community size only in Brazil. Also, β‐diversity of small tropical communities was closer to stochastic expectations compared with β‐diversity of large communities. We suggest that ecological drift may drive variation in some small communities by changing the expected outcome of niche selection, increasing the chances of species with low abundance and narrow distribution to occur in some communities. Habitat destruction, overexploitation, pollution, and reductions in connectivity have been reducing the size of biological communities. These environmental pressures might make smaller communities more vulnerable to novel conditions and render community dynamics more unpredictable. Incorporation of community size into ecological models should provide conceptual and applied insights into a better understanding of the processes driving biodiversity.